Nanotechnology in Agriculture: Which Innovation Potential Does It Have? - Fraceto, Leonardo F.; Grillo, Renato; de Medeiros, Gerson A.; Scognamiglio, Viviana; Rea, Giuseppina; Bartolucci, Cecilia (Frontiers in Environmental Science, 2016)
Recent scientific data indicate that nanotechnology has the potential to positively impact the agrifood sector, minimizing adverse problems of agricultural practices on environment and human health, improving food security and productivity (as required by the predicted rise in global population), while promoting social and economic equity. In this context, we select and report on recent trends in nanomaterial-based systems and nanodevices that could provide benefits on the food supply chain specifically on sustainable intensification, and management of soil and waste. Among others, nanomaterials for controlled-release of nutrients, pesticides and fertilizers in crops are described as well as nanosensors for agricultural practices, food quality and safety.